Concept of Criminal Policy and Improvement of Criminal Law and Criminal Procedure Law - I. N. Kondrat (Vestnik MGIMO-Universiteta)
The paper is concerned with the modern concept of the criminal policy of the Russian state from the standpoint of determining the main directions of improving the criminal and criminal procedural law.